Validating an Immersive Virtual Environment for Learning 3D Transformations: From Design to Student Impact to Expert Evaluation - Alobaid, Maha Abdulaziz; Manzke, Michael (VTT Technical Research Centre of Finland, 2025)
3D transformations are essential in computer graphics but remain difficult for students to master due to their abstract and spatially complex nature. This work presents a three-phase research study on the design, implementation, and validation of an immersive virtual environment that supports the learning of 3D transformations through direct interaction and real-time visual feedback with 3D objects. The study began with the design and pilot study of the tool, followed by a main study that assessed its impact on spatial skills and conceptual understanding among computer science students. To further validate its educational value, a survey was conducted with university educators experienced in teaching computer graphics and related disciplines. Findings across all studies indicate that the immersive environment is effective and engaging for supporting students’ understanding of 3D transformations. This work contributes to the growing field of XR in computing education and offers evidence-based insights for future integration into teaching and learning practices.
The 22nd EuroXR International Conference (EuroXR 2025)
PUBLISHED
Winterthur, Switzerland
Keywords: Computer Graphics; 3D Transformations; Virtual Reality; Immersive Virtual Environment; Spatial Skills; Creative Technologies; Computer Science; Development; Education